2017
DOI: 10.1186/s13049-017-0409-6
|View full text |Cite
|
Sign up to set email alerts
|

A patient-safety and professional perspective on non-conveyance in ambulance care: a systematic review

Abstract: BackgroundThis systematic review aimed to describe non-conveyance in ambulance care from patient-safety and ambulance professional perspectives. The review specifically focussed at describing (1) ambulance non-conveyance rates, (2) characteristics of non-conveyed patients, (3) follow-up care after non-conveyance, (4) existing guidelines or protocols, and (5) influencing factors during the non-conveyance decision making process.MethodsWe systematically searched MEDLINE, PubMed, CINAHL, EMBASE, and reference lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
212
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(230 citation statements)
references
References 92 publications
(297 reference statements)
11
212
5
2
Order By: Relevance
“…It could also aid in patient handovers from EMS to hospitals where a number of issues of transfer of both written and verbal information were noted in a recent review . Even though there is strong evidence that the speed of the initiation of the treatment is of vital importance for the therapeutic outcome, a significant proportion of the patients encountered by EMS are not transported at all . From patient safety and medicolegal perspective it would be reasonable to standardise the physiological evaluation of the patient, especially when EMS personnel are considering not transporting the patient.…”
Section: Discussionmentioning
confidence: 99%
“…It could also aid in patient handovers from EMS to hospitals where a number of issues of transfer of both written and verbal information were noted in a recent review . Even though there is strong evidence that the speed of the initiation of the treatment is of vital importance for the therapeutic outcome, a significant proportion of the patients encountered by EMS are not transported at all . From patient safety and medicolegal perspective it would be reasonable to standardise the physiological evaluation of the patient, especially when EMS personnel are considering not transporting the patient.…”
Section: Discussionmentioning
confidence: 99%
“…This, to some extent, reflects findings from other research concerning a more general patient population. A recent review by Ebben et al [24] found that factors influencing a non-conveyance decision are related to the professional's competence and experience, the patient's health status and best interest, the healthcare system and the availability of decision support.…”
Section: Discussionmentioning
confidence: 99%
“…Ambulance staff are looking for colleagues whom they feel confident in order to talk about their feelings (Ahl et al, 2005;Jonsson & Segesten, 2004;Svensson & Fridlund, 2008). Ambulance staff are constantly exposed to new situations where assessments and decisions have to be made; hence, there is an understanding of the collegial importance both practical and in terms of confidence (Ebben et al, 2017).…”
Section: Discussionmentioning
confidence: 99%